MATERIALIZING MAKERSPACES: QUEERLY COMPOSING SPACE, TIME, AND (WHAT) MATTERS - West-Puckett, Stephanie J. (East Carolina University, 2017)
This dissertation project explores makerspaces as non-traditional composing networks where makers work with (and against) unconventional digital and physical materials such as vinyl, cut paper, plastic filament, insects, Xacto blades, pipe cleaners, reclaimed wicker baskets, DNA, Python code, memes, and Raspberry Pi’s. Choosing materiality over multimodality as the best frame for understanding the material-discursive composing practices of makers, I build a queer- and feminist-inflected new materialist research methodology that orients attention toward embodiment, affect, and the production of difference in composing networks. Using playful, game-based data collection protocols, in conjunction with more traditional data sources, as well as three-dimensional analysis models crafted from foam board, yarn, safety pins, and paper, I document and analyze the material and affective dimensions of composing to build case studies around two diverse maker networks. The first case details participants’ making and composing experiences as part of a connectivist MOOC designed to increase STEM/STEAM literacies for underserved youth and youth educators. The second explores high school students’ experiences in “pop-up” makerspaces that are oriented toward 3D fabrication and prototyping; circuitry, robotics, and computer coding; and upcycling discarded objects and everyday waste for new audiences, purposes, and contexts. Both case studies address the following research questions: Who and what gets to make? Who and what gets made? What drives composition (as process and product) in the network? These questions are essential for understandings issues of representation, access, and equity in contemporary maker networks. The findings of this dissertation materialize “making” as more than a boot-strapping rhetoric that sponsors middle class white male literacies. They underscore the collective values, stances, and practices that are necessary for composing networks to become networkings which are capable of materializing a diversity of bodies and objects. This project turns Writing Studies toward a more material, embodied, and affective understanding of composing, and points to the need to rethink normative composition pedagogies that work to foreclose diversity, creativity, and experimentation. I conclude this project by articulating a queer material rhetoric I call composing sideways: this rhetoric makes space for lateral thinking, feeling, and composing practices which focus on composing the here and the now, and resisting vertical transfer as the most important pedagogical outcome for a writing classroom.
Keywords: making; maker education; queer rhetorics; materiality; new materialisms; object-oriented rhetorics; playful methods; data visualization; community-based research; Maker movement in education; Makerspaces; Homosexuality and education; MOOCs (Web-based instruction); Queer theory